PENGEMBANGAN PROTOTIPE PETA INTERAKTIF BERBASIS SISTEM INFORMASI GEOGRAFIS (SIG) SEBAGAI MEDIA PROMOSI EKOWISATA BAHARI KEPULAUAN BANGKA BELITUNG - Salsabila Hanandita; Atikah Nurhayati; Fanny Kristiadhi; Mochamad Candra Wirawan Arief; Ahmad Prawira Dhahiyat (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
The Bangka Belitung Islands province has great marine ecotourism potential, but the presentation of tourism information remains poorly integrated digitally and spatially. This study aims to identify the distribution and classification of priority tourist attractions and design a prototype of an interactive map based on Geographic Information Systems (GIS) as a digital promotional medium and tourism education. The study uses a mixed-methods approach, with qualitative dominance at the design stage and quantitative support at the prototype evaluation stage. Spatial data processing was carried out using QGIS, the QGIS2Web plugin, and the Leaflet library, while prototype testing involved 30 respondents and employed descriptive analysis, validity and reliability assessments, and Pearson correlation tests in SPSS. The results showed that 33 priority tourist attractions were dominated by coastal areas and beach tourism. All instrument items were declared valid and reliable, with a Cronbach's alpha of 0.944. The test results showed that all indicators were in the